Faktor Risiko Kejadian Nyeri Punggung Bawah Akibat Pekerjaan Pada Fisioterapis Kota Pekanbaru Tahun 2017 - Dedi Afandi; Endang Purnawati Rahayu; Yose Rizal (Jurnal Ilmiah Fisioterapi, 2022)
Low back pain is a major health problem in the workforce. Physiotherapist is a profession that presents a high risk of suffering from low back pain due to work because their work requires the musculoskeletal system, repetitive movements of the upper limbs that the body is in a static and dynamic position for a long time. The purpose of this study was to determine which risk factors were responsible for lower back pain caused by the work of physiotherapists in Pekanbaru. This research uses quantitative methods. The analysis of the data was performed on the analysis of the level of back pain, the analysis of the work picture, the RULA assessment (Rappid Upper Limb Assesment), univariate analysis, bivariate analysis and multivariate analysis. The sample of this study included 42 members of the Pekanbaru City Physiotherapy Association. The results obtained indicate that the variables associated with the incidence of work-related low back pain are sport routines. The results of the analysis obtained interaction variables (p <0.05) Sports Routines so that conclusions can be drawn variables related to the incidence of low back pain is Sports Routines. Physiotherapists who don't exercise regularly are 16 times more likely to experience back pain compared to physiotherapists who exercise regularly. Multivariate results R square = 0.389 means that awkward posture, length of service and gender variables can explain the variable back pain by 38.9%. From the results of this study, it is necessary to educate and modify the working techniques of the physiotherapists of the city of Pekanbaru.